FAKTOR-FAKTOR YANG MEMPENGARUHI PERKAWINAN USIA DINI DI KECAMATAN SUKADANA - Rika Nur Vidalia; Muhammad Azinar (Jurnal Kesehatan Masyarakat (Undip), 2022)
Early marriage is marriage in adolescent under the age of 19 who should not be ready to carry out marriage. Problems with early marriages also occur in Sukadana District. During the period of 2020, there were 283 early marriages. Early marriage can pose risks for both teenagers who marry early, children to be born, and have a risk of divorce. This study aims to determine the factors that influence early marriage in Sukadana District, East Lampung Regency in 2020. This type of research is analytic observational with a cross sectional design. The sample set is 166 respondents with simple random sampling technique. The instruments used are structured questionnaires and observation sheets. Data were analyzed using chi-square test and logistic regression test using SPSS version 20.0. Variables related to early marriage in this study were education level (p=0.004, RP=0.796), parents' occupation (p=0.000, RP=0.237), family income (p=0.001, RP=3.957), and level of knowledge (p=0.000, RP=9.913). While the factors that are not related to early marriage are culture (p=0.710, RP=1.373) and the role of peers (p=0.163, RP=0.604). Early marriage is one of the threats to the achievement of the 2030 Sustainable Development Goals (SDGs) target. To overcome this, it is necessary to have cooperation from various parties to seek to prevent an increase in the incidence of early marriage as a preventive effort to reduce the disturbances and risks that can occur. due to early marriage.